Women, political parties and social movements in South Asia - Amrita Basu (United Nations Research Institute for Social Development (UNRISD), 2005)
This paper will explore two sets of relationships that have until now received relatively little scholarly attention: between women and political parties, and between political parties and social movements that organize women. The focus of this paper will be on South Asia, with case studies of Pakistan, Bangladesh, Sri Lanka and, given the area of expertise of the author, particularly India. The paper will address a range of issues concerning women, parties and movements in South Asia. First, what determines the success of political parties in recruiting, retaining and promoting women? To what extent are there systematic differences between parties of the left, right and centre, and between national and regional parties in this regard? How common and effective are quotas for increasing women's representation within parties? How effectively have the women's wings of political parties defended women's interests? A second issue concerns the strategies that parties adopt to gain women's support during elections. Parties have increasingly directed their appeals at particular groups, including women, by addressing their distinctive interests and identities and by having women organize electoral campaigns. At what point, if any, do parties that receive significant support from women feel compelled to represent their interests? To what extent have women's movements exploited parties' need for women's votes by pressuring them to address certain issues or to honour their pre-election commitments? Third, what is the relationship between women's leadership and women's representation in political parties? From Srimavo Bandranaike to Chandrika Kumaratunga, Khaleda Zia, Sheikh Hasina, Indira Gandhi and Benazir Bhutto, South Asia has had the largest number of female heads of state of any region in the world. What impact have they had on women's participation in party politics during their tenure in office? What are the systemic or structural obstacles to their effectiveness? A fourth issue concerns relationship between political parties and social movements. How successful have women's movements been when they have tried to strengthen parties' commitments to gender equality? A second kind of social movement with which parties have allied in the ethnic/religious movement. What implications has this had for women's participation?
Keywords: 330